Optimalisasi Pendidikan Kesehatan Pada Lansia Hipertensi Dengan Massage Swedia Di Gedung Pusat Kegiatan Penyantunan Usia Lanjut Aisiyah Surakarta - ERMAWATI, MUZAROAH (Bhakti Sabha Nusantara, 2023)
Increasing age can cause a decline in several physical and psychological functions experienced as a result of the aging process, including causing health problems for the elderly. Hypertension is a disease that often occurs in the elderly. Efforts can be made to improve blood pressure with Swedish Massage therapy which is useful in providing a relaxation response and is also able to reduce blood pressure. The aim of implementing community service activities is to increase understanding and independence in the elderly using Swedish Massage techniques. The program method for implementing community service will be carried out from March to May 2023 directly by providing materials and Swedish Massage simulations. The results obtained by the elderly were able to understand hypertension and were able to carry out Swedish Massage simulations in accordance with Standard Operational Procedures.